Small is beautiful: economics as if people mattered - Schumacher, Ernst Friedrich (Blond & Briggs, 1973)

Managing Rural Development: Ideas and Experience from East Africa - Chambers, Robert (Scandinavian Institute of African Studies, 1974)
Google-Books-ID: W4IsAAAAMAAJ

Managing Rural Development - Chambers, Robert (Institute of Development Studies Bulletin, 1974)
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1759-5436.1974.mp6001002.x

Inside Foreign Aid - Tendler, Judith (The Johns Hopkins University Press, 1975)
A classic, important study in the anthropology of development, grounded in the author's own work within USAID, and analysis of the organizational and institutional pressures that constrain and shape development agency employees' cognition and action.
Keywords: IMPORTANT